2014
DOI: 10.1371/journal.pone.0105670
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction to Social Stress in Social Phobia: Discordance between Physiological and Subjective Parameters

Abstract: BackgroundResearch on the biopsychological background of social phobia (SP) is scarce and inconsistent. We investigated endocrine and autonomic markers along with subjective responses to a standardized stress situation (Trier Social Stress Test, TSST) in SP patients and healthy controls (HC).MethodsWe examined 88 patients with the primary diagnosis of SP as well as 78 age and sex comparable HCs with the TSST. Blood and saliva samples were obtained before and after the TSST for the assessment of salivary cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 46 publications
5
40
3
1
Order By: Relevance
“…A recent meta-analytic review of RSA across multiple psychiatric diagnoses, including anxiety disorders, found reduced RSA in adults with psychiatric diagnoses and controls at baseline or in response to a stressor, including unmedicated adults (Alvares et al 2016). However, other studies in samples of undergraduate students have not found RSA differences between adults with high versus low trait anxiety (Wilhelm et al 2001), and the only study to employ the TSST in adults with anxiety disorders reported no differences between adults with anxiety disorders and those without (Klumbies et al 2014). Similar to the adult literature, studies of children with anxiety disorders have suggested lower PNS functioning at baseline (Dieleman et al 2015).…”
Section: Discussionmentioning
confidence: 92%
“…A recent meta-analytic review of RSA across multiple psychiatric diagnoses, including anxiety disorders, found reduced RSA in adults with psychiatric diagnoses and controls at baseline or in response to a stressor, including unmedicated adults (Alvares et al 2016). However, other studies in samples of undergraduate students have not found RSA differences between adults with high versus low trait anxiety (Wilhelm et al 2001), and the only study to employ the TSST in adults with anxiety disorders reported no differences between adults with anxiety disorders and those without (Klumbies et al 2014). Similar to the adult literature, studies of children with anxiety disorders have suggested lower PNS functioning at baseline (Dieleman et al 2015).…”
Section: Discussionmentioning
confidence: 92%
“…We based our hypothesis on preclinical work demonstrating that estradiol inhibits HPA axis reactivity, and also stimulates the production of CBG and lowers unbound cortisol levels (Dayas et al, 2000; Minni et al, 2014). Also, some TSST studies showed that healthy women using oral contraceptives, which contain high levels of estradiol, had cortisol responses lower than men and similar to follicular women (e.g, Cornelisse et al, 2011; Kirschbaum et al, 1999; but not Klumbies et al, 2014). Given this evidence, the lack of association in this study was somewhat surprising.…”
Section: Discussionmentioning
confidence: 99%
“…While self‐reported anxiety increased in patients with SAD before, during, and after Trier Social Stress Test (TSST), differences in the biological stress response (sAA, HR, and heart rate variability [HRV]) were not observed between the SAD and healthy controls (Klumbies et al. 2014). In another study, there were no significant differences between SAD subjects and controls in terms of TSST (Martel et al.…”
Section: Introductionmentioning
confidence: 99%